Education About Correct Exercise and the Effectiveness of Measuring Pulse Rate Before, During and After Exercise - Gilang Nuari Panggraita; Mega Widya Putri; Idah Tresnowati; Lukman Alfaris (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Exercise is highly essential to maintain good health, especially in the current era heavily reliant on technology. Moreover, with the ongoing COVID-19 pandemic that has led to changes in the education system, shifting from in-person to online learning, the use of gadgets has surged while physical activities like sports have declined. The increased use of gadgets underscores the need for awareness and education regarding the importance of exercise and how to do it correctly. This outreach program aims to enhance understanding of the significance of exercise and proper exercise techniques, as well as improve knowledge and skills in setting exercise goals and measuring heart rate before, during, and after physical activity.This program was attended by 60 participants who were 11th-grade students from SMA N 1 Pekalongan. The activity took place on Saturdays, starting from 8:00 AM to 2:00 PM. The outreach team consisted of four lecturers and two students from the Physical Education Program at Muhammadiyah University Pekajangan Pekalongan. Based on the pre-test and post-test results, there was an improvement in participants' understanding of proper exercise techniques and the effectiveness of heart rate measurement before, during, and after exercise. In conclusion, students' understanding of the importance of proper exercise and its relation to heart rate measurement needs to be enhanced, and one effective way is through educational activities, training, and guidance. These activities aim to empower students to engage in independent physical activity and reduce the use of gadgets that contribute to sedentary behavior in today's generation. Additionally, some recommendations for schools as part of the follow-up plan include increasing the quantity of physical activities within the school environment, optimizing the promotion of a healthy and active lifestyle among students, and teachers serving as role models for students in maintaining health and fitness through proper exercise.